You no longer control your brand. Issue 7 (8th June 2015) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – To draw parallels between the development of brand identity by successful contemporary artists and the use by mainstream companies of social and ethical factors or product innovation to act as a focus for their brand narrative. Design/methodology/approach – Analyzes the workings of the art market and provides examples of brand development by celebrity artists. Discusses the relationships between social, cultural, and economic capital and shows how this distinction can be profitably used in the development and marketing of consumer products. Findings – Marketing ain't what it used to be. That tightly controlled brand identity is a thing of the past. In an era dominated by social media, everyone – but everyone – can share their opinion on what your brand stands for. Supporters, detractors, activists […] like them or loathe them, you need to know how this model works if you want to grow the business. Practical implications – Shows how the development of symbolic capital can subsequently lead to financial success when marketers highlight company characteristics that appeal to their target market rather than emphasizing the profit motive. Social implications – Advocates paying less attention to "what the consumer thinks they want" and more to marketing creative concepts. Originality/value – Proposes a departure from traditional marketing theory and practices. Recommends that companies become more product-focused in order to achieve a higher rate of innovation.